Application of comprehensive 2-dimensional liquid chromatography for the analysis of complex phenolic fractions - Kalili, Kathithileni Martha (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.